Bad Software Architecture Is a People Problem. - MATSUDAIRA, KATE (Communications of the ACM, 2016)
The article explores the notion of bad software architecture. Particular focus is given to how this relates to interpersonal relations including back-end team managing and the front-end team consuming the data. Additional topics discussed include APIs (Application Programming Interface), insights on managing teams of software developers and working together to solve bugs.